Targeted Expression of miR-7 Operated by TTF-1 Promoter Inhibited the Growth of Human Lung Cancer through the NDUFA4 Pathway - Liangyu Lei; Chao Chen; Juanjuan Zhao; HaiRong Wang; Mengmeng Guo; Ya Zhou; Junming Luo; Jidong Zhang; Lin Xu (Elsevier, 2017)
Targeted expression of gene technique is an important therapeutic strategy for lung cancer. MicroRNA-7 has been well documented as a promising tumor suppressor but never been test in specific gene-promoter-targeted expression in cancer gene therapy. Here, we first evaluated the efficacy of miR-7 expression operated by the promoter of TTF-1, a lineage-specific oncogene in lung cancer, in vitro using an eukaryotic vector of TTF-1-promoter-operated expression of miR-7 (termed as p-T-miR-7). Interestingly, using a nude mice model, the growth and metastasis of human lung cancer cells in vivo were significantly reduced in remote hypodermic injection of the p-T-miR-7 group, accompanied by increased expression of miR-7 and reduced transduction of the Akt and Erk pathway in situ. Mechanism aspect, global gene expression analysis showed that downregulation of NDUFA4, a novel target of miR-7, contributed to the effects of miR-7 expression operated by TTF-1 promoter on the growth and metastasis of human lung cancer cells, as well as altered transduction of the Akt and Erk pathway. Finally, there was no significant difference in weight or histopathology of other organs. These data provided a basis for development of novel modality of miRNA-based targeted expression therapy against clinical lung cancer. Keywords: miR-7, TTF-1, 95D cells, lung cancer, growth, NDUFA4